DEVELOPMENT OF THE COOLING SYSTEM OF THE SCREW EXTRUDER BODY OF THE 3D PRINTER - ПОЛІЩУК, А. О. (Technologies and Engineering, 2024)
Purpose. The development of a cooling system for the 3D-printer screw extruder housing, which is aimed at reducing the overheating of the polymer material during extrusion and increasing the accuracy and quality of printing finished parts. Methodology. A complex of theoretical, empirical, and statistical methods was used in the work to implement the proposed tasks and test the formulated hypotheses. Theoretical and experimental studies were based on fundamental knowledge in the field of mechanical engineering, heat engineering, and also took into account the features and requirements related to polymer processing. Mathematical processing of the research results was carried out using MS Excel software. Findings. A cooling system for the body of a 3D printer screw extruder has been developed using a material cylinder with fins for heat dissipation, two fans and a thermal barrier. Heat-insulating pads (barriers) for the extruder of a 3D printer made of silicone, Teflon (fluoroplastic 4) and flubon. Their thermal conductivity was studied. With the use of SolidWorks Simulation, a static and transient thermal analysis of the cooling system of the screw extruder body of the 3D printer was performed. A measuring system was developed for setting the temperature of the screw extruder at five points. Experimental studies were conducted to determine the temperature on the nozzle; on the heating element; on the cooling fins of the material cylinder, under the heat-insulating gasket, inside the loading hopper and on its body. Graphs of temperature changes over time in different places of the screw extruder when using different elements of the cooling system are plotted. A comparison of screw extruder temperatures determined theoretically using SolidWorks Simulation and experimentally using a measuring system and a thermal imaging camera was made. Originality. Rational relations between the elements of the cooling system of the screw extruder body of the 3D printer have been established, which make it possible to prevent overheating of the extruder and improve the quality of the extrusion process and the production of finished products. Practical value. A cooling system for the screw extruder body of the 3D printer has been developed, which will significantly increase the efficiency and reliability of the 3D printing process. Such a system will also contribute to increasing the durability of equipment, reducing production costs by preventing defects in 3D printing products associated with temperature fluctuations, and improving their quality. In addition, effective cooling will enable the use of a wider range of polymer materials, including those with higher temperature requirements, thereby expanding the capabilities of 3D printing and providing greater flexibility in manufacturing.